Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the system of equations
[tex]\[ \begin{aligned} -3x + 6y &= 9 \\ 5x + 7y &= -49 \end{aligned} \][/tex]
we aim to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously. Here's a step-by-step solution:
1. Rewrite the first equation:
[tex]\[ -3x + 6y = 9 \][/tex]
This can be divided by 3 for simplicity:
[tex]\[ -x + 2y = 3 \quad \text{(Equation 1')} \][/tex]
2. Rewrite the second equation:
[tex]\[ 5x + 7y = -49 \quad \text{(Equation 2)} \][/tex]
3. Solve Equation 1' for [tex]\(x\)[/tex]:
[tex]\[ -x + 2y = 3 \implies x = 2y - 3 \][/tex]
4. Substitute [tex]\(x = 2y - 3\)[/tex] into Equation 2:
[tex]\[ 5(2y - 3) + 7y = -49 \][/tex]
Simplify this expression:
[tex]\[ 10y - 15 + 7y = -49 \][/tex]
Combine like terms:
[tex]\[ 17y - 15 = -49 \][/tex]
Solve for [tex]\(y\)[/tex]:
[tex]\[ 17y = -49 + 15 \][/tex]
[tex]\[ 17y = -34 \][/tex]
[tex]\[ y = -2 \][/tex]
5. Use [tex]\(y = -2\)[/tex] to solve for [tex]\(x\)[/tex]:
Substitute [tex]\(y = -2\)[/tex] back into Equation 1':
[tex]\[ x = 2(-2) - 3 \][/tex]
Simplify the expression:
[tex]\[ x = -4 - 3 \][/tex]
[tex]\[ x = -7 \][/tex]
So, the solution to the system of equations is [tex]\(x = -7\)[/tex] and [tex]\(y = -2\)[/tex].
Hence, the correct answer is:
D. [tex]\((-7, -2)\)[/tex]
[tex]\[ \begin{aligned} -3x + 6y &= 9 \\ 5x + 7y &= -49 \end{aligned} \][/tex]
we aim to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously. Here's a step-by-step solution:
1. Rewrite the first equation:
[tex]\[ -3x + 6y = 9 \][/tex]
This can be divided by 3 for simplicity:
[tex]\[ -x + 2y = 3 \quad \text{(Equation 1')} \][/tex]
2. Rewrite the second equation:
[tex]\[ 5x + 7y = -49 \quad \text{(Equation 2)} \][/tex]
3. Solve Equation 1' for [tex]\(x\)[/tex]:
[tex]\[ -x + 2y = 3 \implies x = 2y - 3 \][/tex]
4. Substitute [tex]\(x = 2y - 3\)[/tex] into Equation 2:
[tex]\[ 5(2y - 3) + 7y = -49 \][/tex]
Simplify this expression:
[tex]\[ 10y - 15 + 7y = -49 \][/tex]
Combine like terms:
[tex]\[ 17y - 15 = -49 \][/tex]
Solve for [tex]\(y\)[/tex]:
[tex]\[ 17y = -49 + 15 \][/tex]
[tex]\[ 17y = -34 \][/tex]
[tex]\[ y = -2 \][/tex]
5. Use [tex]\(y = -2\)[/tex] to solve for [tex]\(x\)[/tex]:
Substitute [tex]\(y = -2\)[/tex] back into Equation 1':
[tex]\[ x = 2(-2) - 3 \][/tex]
Simplify the expression:
[tex]\[ x = -4 - 3 \][/tex]
[tex]\[ x = -7 \][/tex]
So, the solution to the system of equations is [tex]\(x = -7\)[/tex] and [tex]\(y = -2\)[/tex].
Hence, the correct answer is:
D. [tex]\((-7, -2)\)[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.